NGC 1261: an r-process enhanced globular cluster from the Gaia-Enceladus event - Koch-Hansen, Andreas; Hansen, Camilla Juul; McWilliam, Andrew (Astronomy and astrophysics, 2021)
Our Milky Way (MW) has witnessed a series of major accretion events in the past. One of the later additions, the Gaia-Enceladus merger, has contributed a considerable mass to the inner Galaxy, but also generously donated to the outer halo. So far, associations with present-day MW globular clusters (GCs) have been chiefly based on their kinematics and ages. In this work, we present a chemical abundance study of the outer halo (RGC ∼ 18 kpc) GC NGC 1261, which has been suggested to be an accreted object based on its younger age. We measured 31 species of 29 elements in two stars from high-resolution Magellan/MIKE spectra and find that the cluster is moderately metal poor, at [Fe/H] = −1.26, with a low scatter of 0.02 dex. NGC 1261 is moderately α-enhanced to the 0.3 dex level. While from the small sample alone it is difficult to assert any abundance correlations, the light elements Na, O, Mg, and Al differ significantly between the two stars in contrast to the majority of other elements with smaller scatter; this argues in favor of multiple generations of stars coexisting in this GC. Intriguingly for its metallicity, NGC 1261 shows heavy element abundances that are consistent with r-process nucleosynthesis and we discuss their origin in various sites. In particular the Eu overabundance quantitatively suggests that one single r-process event, such as a neutron-star neutron-star merger or a rare kind of supernova, can be responsible for the stellar enhancement or even the enrichment of the cluster with the excess r material. Its heavy element pattern makes NGC 1261 resemble the moderately enhanced r-I stars that are commonly found in the halo and have been detected in Gaia-Enceladus as well. Therefore, combining all kinematical, age, and chemical evidence we conclude that NGC 1261 is a chemically intriguing GC that was born in the Gaia-Enceladus galaxy and has been subsequently accreted into the MW halo.